Dampak Program Fun Tahfidz Camp Terhadap Kecerdasan Emosional Dan Perilaku Agresif Pada Anak (Studi Kasus : SDIT Daarul Faalah Kota Pariaman) - Irsyadul Fitri; Nurva Dillatul Vatin; Fisa Amanah; M Hubbal Khair (Affection: Journal of Psychology And Counseling, 2024)
This study aims to determine the impact of the fun tahfidz camp program on emotional intelligence and aggressive behavior in children at SDIT Daarul Faalah Pariaman City. This research is qualitative research using a case study approach to find out more deeply and in detail about a problem or phenomenon under study. The subjects in this study were 3 (three) parents whose children behaved aggressively and attended the fun tahfidz camp program. The sampling technique was carried out using purposive sampling which is a subjective or selective assessment sampling of the subject. Furthermore, data collection uses observation, interview and documentation methods. The results of research conducted on 3 (three) subjects and 3 informants, namely parents of children who behave aggressively and 1 (one) informant, namely the teacher (coordinator) of the fun tahfidz camp program at SDIT Darul Faalah Pariaman. This research result show that the fun tahfidz camp program has a positive impact on emotional intelligence and aggressive behavior in children. The increase in emotional intelligence is reflected in changes in children's attitudes and their ability to recognize, express and manage emotions better. This is also reflected in the way they interact with peers, and are able to establish good relationships. In this fun tahfidz camp program, children are taught religious values, positive interactions, self-reflection, mabid (bina taqwa night), watching motivational films together and fun group activities so that children can learn and apply alternative ways to solve problems or conflicts.This shows that this fun tahfidz camp not only focuses on spiritual aspects such as memorizing the Qur'an and reciting the Quran, but also includes social and emotional aspects that are important for child development.